(untitled) (Medical Forum Monthly, 2020)
Objective: Investigating the hepatoprotective effects of Pentoxifylline (PTX) in carbon tetrachloride (CCl4) induced liver injury in rat model. Study Design: Experimental study Place and Duration of Study: This study was conducted at the Animal house of Sindh Agriculture University Tando Jam and Isra University from January 2017 to August 2017. Materials and Methods: 45 male rats were selected by purposive sampling through criteria of inclusion. Animals were housed in stainless steel cages under standard conditions. Rats were divided into Group A (control), Group B (CCl4) and Group C (CCl4 + PTX 200 mg/kg). Blood samples were centrifuged to get sera for the estimation of serum bilirubin, creatinine and liver enzymes. Liver tissue sections (3-5μ thickness) were stained with H & E and Microscopic tissue findings were noted. Statistical software SPSS version 22.0 (IBM corporation) was used for statistical analysis (P≤0.5). Results: Serum bilirubin and creatinine in control group in experimental groups B and C were raised (P<0.05). Pentoxifylline treated group C rats revealed reduction of 65% in ALT, 58% in AST, 48% LDH and 71% ALP (P<0.05). Liver histology was also improved in PTX treated group C (P<0.05). Conclusion: Pentoxifylline shows hepatoprotective potential against chemical induced liver injury, however mechanism of action remains to be elucidated.